Hairy cell leukemia: a 'hair-raising' update. Issue 5 (October 2014) - Topp, Zheng Z; Saven, Alan
<x xml:space="preserve">Abstract</x> Hairy cell leukemia (HCL) is an uncommon low grade B cell leukemia that is marked by pancytopenia, splenomegaly, and characteristic cytoplasmic hairy projections. The current standard of care is treatment with purine analogs, like cladribine or pentostatin, which provide a high complete remission rate with a median duration of response of 5 years. Many patients who show initial remission will relapse, and others with refractory disease may show no response. The discovery of the BRAF mutation has created a therapeutic target exploited by oral inhibitors like vemurafenib and dabrafenib. Targeted immunotoxins remain an interesting area of study. The use of the monoclonal antibody rituximab in combination with purine analogs appears to produce even higher responses, often employed to minimize or eliminate residual disease. With our current understanding of B cell signaling pathways, the development of kinase inhibitors appears promising and may change the future therapeutic landscape of this rare disease.